Tindak Tutur Ekspresif dalam Novel 00.00 Karya Ameylia Falensia - Siska Triananda; Siti Ainim Liusti (AHKAM, 2026)
Although studies on expressive speech acts in literary works have been widely conducted, research linking types of expressive speech acts with speech strategies in contemporary novels remains limited. This study aims to analyze the types of expressive speech acts and speech strategies in the novel 00.00 by Ameylia Falensia. This study employed a qualitative approach with a descriptive design. The research data consisted of 336 character utterances selected through purposive sampling. Data were collected using reading and note-taking techniques, then analyzed using the Miles and Huberman analysis model, which includes data reduction, data presentation, and conclusion drawing. The results showed that there were twelve types of expressive speech acts, with condemning as the dominant type, followed by criticism and complaining. In the aspect of speech strategies, five strategies were identified, with the dominant strategy being bald on-record speech without small talk. These findings indicate that language use in the novel is influenced by emotional conflicts among the characters, so that utterances tend to be delivered directly. This study contributes to the development of pragmatic studies, particularly those related to expressive speech acts and speech strategies in literary works, and also has practical implications for the teaching of Indonesian language and literature. Further research is recommended to expand the object of study and use a corpus-based approach in order to obtain more comprehensive results.